Immune Profile in Blood Following Non-convulsive Epileptic Seizures in Rats - Avdic, Una; Ahl, Matilda; Öberg, Maria; Ekdahl, Christine T. (Frontiers in Neurology, 2019)
Non-convulsive status epilepticus (NCSE) is a prolonged epileptic seizure with subtle symptoms that may delay clinical diagnosis. Emerging experimental evidence shows brain pathology and epilepsy development following NCSE. New diagnostic/prognostic tools are therefore needed for earlier and better stratification of treatment. Here we examined whether NCSE initiates a peripheral immune response in blood serum from rats that experienced electrically-induced NCSE. ELISA analysis showed an acute transient increase in serum protein levels including interleukin-6 6h post-NCSE, similar to the immune reaction in the brain. At 4 weeks post-NCSE, when 75% of the rats also had developed spontaneous seizures, several immune proteins were altered. In particular, CD68, MHCII, and galectin-3 were increased and CD4 decreased in serum compared to both non-stimulated controls and NCSE rats without spontaneous seizures, without correlation to interictal epileptiform activity. Analyses of serum following intracerebral injection of lipopolysaccharide (LPS) showed an acute increase in interleukin-6, but at 4 weeks unaltered levels of MHCII and galectin-3, an increase in CD8 and CD11b and a decrease in CD68. None of the increased serum protein levels after NCSE or LPS could be confirmed in spleen tissue. Our data identifies the possibility to detect peripheral changes in serum protein levels following NCSE, which may be related to the development of subsequent spontaneous seizures.